Comparison of simulation models NRMM and NTVPM for assessing military tracked vehicle cross-country performance. (December 2018) - Wong, J.Y.; Jayakumar, P.; Toma, E.; Preston-Thomas, J.
Highlights: Comparison of the soundness of the methodologies of simulation models NRMM and NTVPM. Evaluation of the adequacy of the input vehicle and terrain parameters of the models. Assessment of the performances predicted by the models with measured data. NTVPM has shown to provide a sound basis for developing the next generation model. Abstract: Mobility of ground vehicles is an important issue for defence operations. In the United States and some other NATO countries, the NATO Reference Mobility Model (NRMM) is currently used to evaluate military ground vehicle mobility. The cross-country performance prediction module of NRMM is based on empirical relations established with test data primarily collected decades ago. It has inherent limitations, such as the uncertainty whether the empirical relations can be extrapolated beyond the test conditions upon which they were derived. This paper describes a comparison of the empirically-based NRMM with the physics-based Nepean Tracked Vehicle Performance Model (NTVPM) for assessing the cross-country performance of military tracked vehicles. It examines the soundness of the methodologies of NRMM and NTVPM, the adequacy of the vehicle design parameters and terrain characteristics that they take into account, the user friendliness of their operations, and the correlations between the measured cross-country performance of a notional tracked vehicle (an armoured personnel carrier) and that predicted by the two simulation models on sandy terrain, muskeg and snow-covered terrain. Based on the results of the evaluation, it appears that the physics-based NTVPM has potential as the basis for the development of the next generation simulation model for assessing the cross-country performance of military tracked vehicles.